Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Explore thousands of questions and answers from a knowledgeable community of experts ready to help you find solutions. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
The definition of the inverse function is
[tex]\begin{gathered} f(f^{-1}(x))=x \\ \text{and} \\ f^{-1}(f(y))=y \end{gathered}[/tex]In our case,
[tex]f(x)=2x-1[/tex]Then,
[tex]\begin{gathered} f^{-1}(f(x))=x \\ \Rightarrow f^{-1}(2x-1)=x \\ \Rightarrow f^{-1}(x)=\frac{x+1}{2} \end{gathered}[/tex]We need to verify this result using the other equality as shown below
[tex]\begin{gathered} f^{-1}(x)=\frac{x+1}{2} \\ \Rightarrow f(f^{-1}(x))=f(\frac{x+1}{2})=2(\frac{x+1}{2})-1=x+1-1=x \\ \Rightarrow f(f^{-1}(x))=x \end{gathered}[/tex]Therefore,
[tex]\Rightarrow f^{-1}(x)=\frac{x+1}{2}[/tex]The inverse function is f^-1(x)=(x+1)/2.
We say that a relation is a function if, for x in the domain of f, there is only one value of f(x).
In our case, notice that for any value of x, there is only one value of (x+1)/2=x/2+1/2.
The function is indeed a function, it is a straight line on the plane that is not parallel to the y-axis.
The inverse f^-1(x) is indeed a function
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.